OH-YEAH^^
Vài giây trước

Này

Bình luận (0)

\(x^2-6x+5=x\left(x-5\right)-\left(x-5\right)=\left(x-5\right)\left(x-1\right)\)

Bình luận (0)

Áp dụng t/c dtsbn:
\(\dfrac{x}{3}=\dfrac{y}{5}=\dfrac{z}{-2}=\dfrac{5x}{15}=\dfrac{3z}{-6}=\dfrac{5x+y+3z}{15+5-6}=\dfrac{12}{14}=\dfrac{6}{7}\)

\(\Rightarrow\left\{{}\begin{matrix}x=\dfrac{6}{7}.3=\dfrac{18}{7}\\y=\dfrac{6}{7}.5=\dfrac{30}{7}\\z=\dfrac{6}{7}.\left(-2\right)=-\dfrac{12}{7}\end{matrix}\right.\)

Bình luận (0)

B

Bình luận (0)
Nguyễn Bảo Anh
3 phút trước

     Giải

70 = 2 . 5.  7

115 = 5 . 23

Bình luận (0)

Khoá học trên OLM của Đại học Sư phạm HN